2007
DOI: 10.1007/s10512-007-0073-4
|View full text |Cite
|
Sign up to set email alerts
|

Content of cosmogenic 7Be in the air layer at the ground at temperate latitudes

Abstract: The 7 Be content was measured in aerosols (once per week) and precipitation (once per month) was monitored as part of the monitoring of the radioactivity of the atmospheric layer near the ground in Rostovon-Don in 2001-2005. Data were obtained on the correlations between the 7 Be volume activity in aerosols and the Wolf number, temperature, and amount of precipitation. The highest correlation coefficients were observed during the spring (k = 1). It was determined that the volume activity of 7 Be changes in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…As it has been said above, the most probable source of 7 Be is the atmospheric fallout that have two well expressed maxima, in spring and in autumn (Buraeva et al, 2007). Over the area of study, young needles appear from end of May to first days of June and they have small leaf area at the beginning.…”
Section: Figmentioning
confidence: 77%
“…As it has been said above, the most probable source of 7 Be is the atmospheric fallout that have two well expressed maxima, in spring and in autumn (Buraeva et al, 2007). Over the area of study, young needles appear from end of May to first days of June and they have small leaf area at the beginning.…”
Section: Figmentioning
confidence: 77%
“…Activity concentrations of 7 Be in the atmospheric layer near the ground reached values between 1 and 10 mBq m À3 (Azahra et al, 2003;Cannizzaro et al, 2004;Ioannidou et al, 2005). In similar studies of 7 Be concentration in near-surface air in Rostov-on-Don (Russia) and in Brisbane (Australia), Buraeva et al (2007) and Doering and Akber (2008) reported that the 7 Be content in atmospheric aerosols near the ground and the 7 Be deposition measurements indicated a seasonal variation of the 7 Be volume activity; i.e. a springesummer maximum and an autumnewinter minimum.…”
Section: Introductionmentioning
confidence: 78%
“…The 7 Be deposition, the 7 Be content in air (atmosphere) near the ground and the content as related to the scavenging mechanism and to removal processes were studied by many authors (e.g. Azahra et al, 2003;Buraeva et al, 2007;Doering and Akber, 2008;Hasegawa et al, 2007;Karunakara et al, 2003;Momoshima et al, 2006;Zhu and Olsen, 2009). They suggested that the seasonal variation of the 7 Be volume activity exhibiting a springesummer maximum and an autumnewinter minimum may be significantly dependent on the precipitation mode.…”
Section: Seasonal Variations Of 7 Bementioning
confidence: 99%
“…The change in the content of 7 Be in air stems from the solar activity and have characteristic seasonal variations and a latitude dependence [1,2]. Because of the fast decay of 7 Be, its activity changes in plants versus synoptic conditions.…”
mentioning
confidence: 99%
“…It is commonly believed that basic reactions leading to the production of beryllium isotopes in the Earth's atmosphere are induced by the interaction 1 of cosmic rays with nuclei of nitrogen and and oxygen [4], which are dominant constituents of atmospheric air. These are the so-called spallation reactions 14 N(p, X) 7 Be, 16 O(p, X) 7 Be, 14 N(n, X) 7 Be, and 16 O(n, X) 7 Be.…”
mentioning
confidence: 99%